Researching Digital Sociality: Using WhatsApp to Study Educational Change - Hany Zayed (Journal of Digital Social Research, 2021)
Digital technologies have become deeply implicated in and constitutive of contemporary social life. They are reshaping who we are and how we associate with one another, and are profoundly reconfiguring social relations, processes, and practices in a host of social spheres, particularly education. With Covid-19 further entrenching this implication and accelerating those changes, we are forced to rethink what research is and how it is done. This article presents a step towards researching a changing sociality using social media. Drawing on fieldwork on the digital transformation of Egyptian education, it argues that and showcases how WhatsApp can be systematically used as a qualitative data collection instrument to examine educational change. This article also situates WhatsApp research within digital ethnographic traditions, unpacks emergent methodological challenges and ethical quandaries, and presents potential ways to manage them. In so doing, it problematizes extant methodological categories (such as participation), entrenched dichotomies (such as private/public space), and epistemological questions (such as research temporality). Using a unique case from the Global South at an exceptional time of (educational) change, this article can help researchers as they think about their questions, design their research, conduct their fieldwork, and maneuver an elusive digital landscape. It informs broader methodological discussions within digital sociology and anthropology (of education), digital ethnography, and social media research. It also informs research in other domains like healthcare, geographies beyond the Global South, and platforms with similar affordances like Telegram.